Effects of loneliness on short video addiction among college students: the chain mediating role of social support and physical activity - Zhe Zhao; Yali Kou (Frontiers in Public Health, 2024)
Loneliness is a common public health problem that affects physical and mental health. Prior research has demonstrated a connection between internet addiction and loneliness. Short video addiction is a novel internet addiction. It is necessary to study the potential psychological mechanisms between loneliness and short video addiction. This study investigated the associations between loneliness and short video addiction, as well as the mediating roles played by social support and physical activity.MethodsA sample of 388 college students was selected, and the questionnaires included the Loneliness Scale Short Version, the Short Video Addiction Scale, the Social Support Scale, and the Physical Activity Scale. The data were analyzed using SPSS for correlation analysis and PROCESS macros for mediation effect analysis.Results(1) Loneliness significantly positively affected short video addiction. (2) The association between loneliness and short video addiction was independently mediated by social support. (3) Physical activity independently mediated loneliness and short video addiction. (4) Social support and physical activity play a chain mediating role in the association between loneliness and short video addiction. Our research improves the literature on loneliness and short video addiction, enhances comprehension of the impacts, and offers college students effective ways to combat the addiction.